2014
DOI: 10.3174/ajnr.a3906
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic Complications after Endovascular Treatment of Cerebral Arteriovenous Malformations

Abstract: BACKGROUND AND PURPOSE:Intracranial hemorrhage is the most severe complication of brain arteriovenous malformation treatment. We report our rate of hemorrhagic complications after endovascular treatment and analyze the clinical significance and potential mechanisms, with emphasis on cases of delayed hemorrhage after uneventful embolization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(46 citation statements)
references
References 25 publications
(50 reference statements)
1
43
1
1
Order By: Relevance
“…Endovascular embolization is not innocent. Published combined procedural morbidity and mortality rates are reported around 10 % also in the more recent series [2,6,13,17,18]. It is unclear whether the risk of subsequent surgical resection decreases correspondingly.…”
mentioning
confidence: 99%
“…Endovascular embolization is not innocent. Published combined procedural morbidity and mortality rates are reported around 10 % also in the more recent series [2,6,13,17,18]. It is unclear whether the risk of subsequent surgical resection decreases correspondingly.…”
mentioning
confidence: 99%
“…Baharvahdat et al reported an 11% complication rate after 846 intervention in 408 patients. New permanent disability and death related to hemorrhage after embolization were reported in 7.6% and 1.6% of patients, respectively (18). A meta-analysis by van Beijnum et al reported that complications leading to persistent neurological deficits or death occurred in 6.6% (range 0% -18%) of patients after AVM embolization (19).…”
Section: Discussionmentioning
confidence: 99%
“…Since the report by Willinsky et al, 19 Onyx has been introduced; neuroendovascular techniques have evolved; and myriad factors, including the Spetzler-Martin grade, periprocedural hemorrhage, deep venous drainage, number of embolized branches, age, absence of neurologic deficit, hemorrhagic presentation, small bAVM size, the presence of deep arterial feeders, eloquent location, the presence of arteriovenous fistula components, and venous penetration of embolic agents, have been associated with endovascular complications and unfavorable outcomes. 15,[19][20][21][22][23] Furthermore, adding to our understanding of the mechanisms underlying complications and their frequencies following bAVM transarterial embolization, Baharvahdat et al 24 noted in their series of 846 cases primarily treated with…”
Section: Discussionmentioning
confidence: 99%
“…Notably, complications did not correlate with increasing Spetzler-Martin grade. 24 Intuitively then, increasing numbers of arterial feeders requiring multiple microcatheterizations and/or multistage procedures, the presence of an arteriovenous fistula component increasing the likelihood of premature venous embolization, and eloquent regions intolerant to insult are likely to be associated with complications and poor outcomes following transarterial embolization.…”
Section: Discussionmentioning
confidence: 99%